Model of legal and constitutional responsibility of the President of the United States in the light of recent experience of the application of the impeachment procedure - Jaskiernia, Jerzy (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of the analysis is the model of legal and constitutional responsibility of the president of the United States in the light of the latest experience of its application to the presidents: Richard M. Nixon, Bill Clinton and Donald Trump. The author focused on the question of how highly politicized this procedure is when the impeachment is formulated by the House of Representatives and judged by the Senate. The conducted analysis does not allow to answer this question unequivocally. The elements of politicization, although undoubtedly present, do not allow to equate this procedure with the model of political responsibility present in parliamentary-cabinet systems.